2020
DOI: 10.1016/j.childyouth.2020.104955
|View full text |Cite
|
Sign up to set email alerts
|

Follow or be followed: Exploring the links between Instagram popularity, social media addiction, cyber victimization, and subjective happiness in Italian adolescents

Abstract: The aim of the study is to investigate the association between Instagram popularity and subjective happiness, and to test the mediating roles of cyber victimization and social media addiction. Methods: We recruited a sample of middle school students (N = 345; 49% males, age M: 13.31 years; SD = 1.42; range = 11-16) who reported having an active Instagram account. We collected the following data: sociodemographic data, Instagram activity indicators and followers/following counts, perceived social media addictio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
58
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 43 publications
(60 reference statements)
6
58
1
3
Order By: Relevance
“…It has been observed that neuroticism (Leong et al 2019 ; Marengo et al 2020 ), depression, and loneliness (Dalvi-Esfahani et al 2019 ) are associated with social media addiction. Users who have more friends and followers (Longobardi et al 2020 ) and receive mostly positive feedback (Marengo et al 2020 ) on social networking sites are at a higher risk of getting addicted to social media. It has also been observed that happiness in real life is negatively associated with social media addiction, while stress in real life is positively associated with social media addiction (Longstreet and Brooks 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that neuroticism (Leong et al 2019 ; Marengo et al 2020 ), depression, and loneliness (Dalvi-Esfahani et al 2019 ) are associated with social media addiction. Users who have more friends and followers (Longobardi et al 2020 ) and receive mostly positive feedback (Marengo et al 2020 ) on social networking sites are at a higher risk of getting addicted to social media. It has also been observed that happiness in real life is negatively associated with social media addiction, while stress in real life is positively associated with social media addiction (Longstreet and Brooks 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been observed that happiness in real life is negatively associated with social media addiction, while stress in real life is positively associated with social media addiction (Longstreet and Brooks 2017 ). Furthermore, people who use social media actively (Longobardi et al 2020 ) and people with higher daily screen time (Chung et al 2019 ) are more susceptible to social media addiction.…”
Section: Introductionmentioning
confidence: 99%
“…First, pubertal maturation necessarily engenders threats to female adolescent’s body esteem due to unwanted bodily changes [ 19 ] such as increased body fat [ 20 ]. Second, according to Longobardi et al’s [ 21 ] recent findings, adolescents rely on indicators of appearance-focused popularity to fulfil their psychological needs such as peer acceptance or social status. Third, interwoven with their psychological need for social acceptance, physical appearance is a salient factor that influences self-worth of female adolescents [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of course, young people can use social networks to keep in touch with their peers, but we must warn that the excessive use of social media can increase distress and the risk of victimization and have an impact on the psychological well-being of children (Longobardi et al, 2020a , b ). We must also assume that at greater risk will still be the low-rise adolescents in social status such as popularity, rejection, and social exclusion.…”
mentioning
confidence: 99%
“…We must also assume that at greater risk will still be the low-rise adolescents in social status such as popularity, rejection, and social exclusion. In fact, the literature seems to indicate that children who are rejected and excluded from their peer groups seem to experience the same dynamic even in the virtual world (Longobardi et al, 2020a ). Therefore, the quarantine situation could increase the sense of exclusion and isolation and, in turn, increase suicidal risk (Morese and Longobardi, 2020 ).…”
mentioning
confidence: 99%